The development of a biosensor for the detection of PS II herbicides using green microalgae - Mohamed, Maizatul Suriza; Ampon, Kamaruzaman; Anton, Ann (Penerbit Universiti Sains Malaysia, 2004)
Increasing concern over the presence of herbicides in water body has stimulated research towards the development of sensitive method and technology to detect herbicides residue.